IJCM_8A: Prevalence of anemia among pregnant women in selected health blocks of Himachal Pradesh - Negi Ashwani; Gandhi Manoj K. (Wolters Kluwer Medknow Publications, 2024)
Background: Anemia is a manifestation of under-nutrition and poor dietary intake of iron and is a public health problem in India. Iron deficiency is the primary cause of anemia among women in India with a prevalence reported in National Family Health Survey-4 as 54.4% among pregnant women and 52.2% among women of age 15-49 years in rural area. Objectives: To estimate the prevalence of anemia among pregnant women in selected health blocks of Himachal Pradesh. Methodology: It was a community based cross-sectional study where 09 health blocks from 07 districts were selected randomly using probability proportionate to size criteria for selection of blocks. Considering 50% prevalence, 5% error and 80% Confidence level, a sample size 164 was obtained and taking 10% dropout a total sample size of 180 was obtained. 20 pregnant women from each block were enrolled after written informed consent and screened for anemia. Results: A total of 180 women were enrolled for the study. The mean age of the study subjects was 26.3±4.13 years with mean age of marriage as 22.44±2.97 years. 102 (56.6%) subjects were primigravida. The prevalence of anemia observed was 29.4% and mean hemoglobin levels observed were 11.7±1.47 gm/dL. Conclusion: We estimated prevalence of anemia among pregnant women as 29.4% which is lower than that reported in India but still there are lacunas which are to be filled so as to further reduce its prevalence.